Life after ponatinib failure: outcomes of chronic and accelerated phase CML patients who discontinued ponatinib in the salvage setting. Issue 6 (3rd June 2018) - Boddu, Prajwal; Shah, Abdul Rashid; Borthakur, Gautam; Verstovsek, Srdan; Garcia-Manero, Guillermo; Daver, Naval; Kadia, Tapan; Ravandi, Farhad; Jain, Nitin; Alhuraiji, Ahmad; Burger, Jan; Kornblau, Steven; et al.
Abstract: Ponatinib is a pan-tyrosine kinase inhibitor (TKI) with efficacy in multirefractory CML patients who have failed other TKIs. Despite excellent response rates, resistance or intolerance may develop. We conducted a retrospective review of the outcome of patients with chronic (CP) and accelerated (AP) phase CML refractory to prior TKI who discontinued ponatinib for resistance or intolerance. Nineteen CP patients, discontinued due to resistance ( n  = 13), toxicity ( n  = 5) and to pursue stem cell transplantation ( n  = 1). At discontinuation, 14 were still in CP, three had progressed to AP and two to blast phase (BP). Three CP patients improved their cytogenetic response (CyR) to complete CyR (CCyR), two after SCT and one on omacetaxine. None of the 12 patients, without a major cytogenetic response at ponatinib discontinuation, including all patients treated with subsequent TKIs, responded to therapy. Seventeen AP patients, stopped ponatinib due to resistance ( n  = 15) or intolerance ( n  = 2). At discontinuation, 14 were still in AP and three had progressed to BP. Four patients were treated with SCT and one achieved major molecular response. None of the 12 patients treated with non-SCT approaches responded to subsequent therapy. Median survival for all patients was 16.6 months after ponatinib discontinuation (31, 9 and 13 months for patients in CP, AP and BP, respectively). Median survival was 60 months for patients who discontinued ponatinib for toxicity and 11 months for those who discontinued for resistance. Long-term outcome of patients with ponatinib failure are poor with estimated one-year OS and EFS rates of 54% and 40%, respectively. New treatment options are required for this subset of patients.